The importance of patient-centered care and co-creation of care for satisfaction with care and physical and social well-being of patients with multi-morbidity in the primary care setting - Sanne Jannick Kuipers; Jane Murray Cramm; Anna Petra Nieboer (BMC, 2019)
Abstract Background Patients with multi-morbidity have complex care needs that often make healthcare delivery difficult and costly to manage. Current healthcare delivery is not tailored to the needs of patients with multi-morbidity, although multi-morbidity poses a heavy burden on patients and is related to adverse outcomes. Patient-centered care and co-creation of care are expected to improve outcomes, but the relationships among patient-centered care, co-creation of care, physical well-being, social well-being, and satisfaction with care among patients with multi-morbidity are not known. Methods In 2017, a cross-sectional survey was conducted among 216 (of 394 eligible participants; 55% response rate) patients with multi-morbidity from eight primary care practices in Noord-Brabant, the Netherlands. Correlation and regression analyses were performed to identify relationships among patient-centered care, co-creation of care, physical well-being, social well-being, and satisfaction with care. Results The mean age of the patients was 74.46 ± 10.64 (range, 47-94) years. Less than half (40.8%) of the patients were male, 43.3% were single, and 39.3% were less educated. Patient-centered care and co-creation of care were correlated significantly with patients' physical well-being, social well-being, and satisfaction with care (all p ≤ 0.001). Patient-centered care was associated with social well-being (B = 0.387, p ≤ 0.001), physical well-being (B = 0.368, p ≤ 0.001) and satisfaction with care (B = 0.425, p ≤ 0.001). Co-creation of care was associated with social well-being (B = 0.112, p = 0.006) and satisfaction with care (B = 0.119, p = 0.007). Conclusions Patient-centered care and co-creation of care were associated positively with satisfaction with care and the physical and social well-being of patients with multi-morbidity in the primary care setting. Making care more tailored to the needs of patients with multi-morbidity by paying attention to patient-centered care and co-creation of care may contribute to better outcomes.